2011
DOI: 10.2737/nrs-rb-58
|View full text |Cite
|
Sign up to set email alerts
|

Maryland's Forests 2008

Abstract: The fi rst full annual inventory of Maryland's forests reports approximately 2.5 million acres of forest land, which covers 40 percent of the State's land area and with a total volume of more than 2,100 cubic feet per acre. Nineteen percent of the growing-stock volume is yellow-poplar, followed by red maple (13 percent) and loblolly pine (10 percent). All species of oaks combined account for 26 percent of the total growing-stock volume. Yellow-poplar volume is increasing, particularly in the large-diameter cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Most of the forested land cover on Maryland's Lower Eastern Shore is secondary growth and, at one time, was under intensive agricultural use before it was converted back to forest (Lister et al. ). For comparison, DOP background concentrations in soil porewater of forests without a legacy of fertilizer inputs are often an order of magnitude lower than those measured in this study (0.02 mg P/L; Qualls and Haines , Qualls et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the forested land cover on Maryland's Lower Eastern Shore is secondary growth and, at one time, was under intensive agricultural use before it was converted back to forest (Lister et al. ). For comparison, DOP background concentrations in soil porewater of forests without a legacy of fertilizer inputs are often an order of magnitude lower than those measured in this study (0.02 mg P/L; Qualls and Haines , Qualls et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Lister et al. ). Tidal salt marshes cover about 15% of Somerset County and are located along its coastline (Shepard et al.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…LULCC and disturbance caused a loss of 1.11 ± 0.35 Pg C yr −1 annually [32]. Lister et al [33] indicated that the Chesapeake Bay Basin had a net loss of 2% of forest land since the 1980s. Claggett et al [25] predicted that, to a large extent, forests in the Gulf region of CBW will be severely disrupted in the coming decades because of development pressure.…”
Section: Discussionmentioning
confidence: 99%